"Doing prescribing": how might clinicians work differently for better, safer care. (26th November 2003) - Elwyn, G; Edwards, A; Britten, N
Abstract : Prescribing medicines is a cornerstone of medical practice. There is, however, ample evidence that the prescribing process is far from ideal when viewed from the perspective of patients who wish to understand why they should take medicine, what potential harm they might face, and how they might integrate medicine taking into the pattern of their life, beliefs, and attitudes. Misalignment between clinicians and patients about medicine taking leads to a multitude of problems. Recently, a concept known as concordance has been suggested, where the prescribing interaction is seen as a process where both the patient and professional views and beliefs about medication, and the associated harms and benefits, are shared and negotiated. This interaction depends on a communication process that is becoming known as shared decision making between clinicians and patients. Although there is as yet little evidence that this approach leads to improved clinical outcomes, ethical principles and the core values of medical practice suggest that involving patients in the prescribing process will lead to better, safer care.